2011
DOI: 10.1080/19317611.2011.562278
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and Sexual Behavior Comparisons of Indian and U.S. Internet Samples of Men who have Sex with Men

Abstract: Data were collected via the Internet on sexual behaviors of Indian men who have sex with men (MSM; n = 171); these data were compared to online American MSM (n = 682). Among Indian MSM, 51% had never been tested for HIV, 100% believed themselves to be HIV-uninfected, and 22% (secondary Internet male partners) to 43% (primary male partners) reported not using condoms during last anal intercourse. While U.S. MSM were more likely to not use condoms (42% for secondary Internet partners to 67% for primary male part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
1
8
1
Order By: Relevance
“…In addition, fewer men report receptive oral sex from male (and female) sexual partners than those who report having “given” oral sex. This differs from prior reports from MSM samples in India where receptive oral sex was a commonly reported sexual act (Welles et al, 2011). Our data also challenge the prevailing notion in India that men engage in same-sex behavior mainly because they do not “receive” unconventional sexual pleasure (e.g., oral sex) from their female sex partners, wives and girlfriends.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, fewer men report receptive oral sex from male (and female) sexual partners than those who report having “given” oral sex. This differs from prior reports from MSM samples in India where receptive oral sex was a commonly reported sexual act (Welles et al, 2011). Our data also challenge the prevailing notion in India that men engage in same-sex behavior mainly because they do not “receive” unconventional sexual pleasure (e.g., oral sex) from their female sex partners, wives and girlfriends.…”
Section: Discussioncontrasting
confidence: 99%
“…Welles et al (2011) also highlighted behavioral differences between internet-using Indian MSM and their western counterparts. With limited research-based insights into demographics, risk and identities of internet-using Indian MSM and transgenders/ hijras , it is crucial to investigate HIV- and sexuality-related knowledge, attitudes, beliefs and behaviors particularly as this population may also not ascribe to traditional sexual identities adopted by the much-researched Indian MSM and transgenders/h ijra population on physical sites who fall within the reach of traditional HIV interventions.…”
Section: Introductionmentioning
confidence: 98%
“…In India, only two studies (Jethwani, Mishra, Jethwani, & Sawant, 2014; Welles et al, 2011) have explored identity differences between internet-using MSM and MSM investigated by other studies in India. Welles et al (2011) also highlighted behavioral differences between internet-using Indian MSM and their western counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have documented diverse sexualities among men in India, including those that are not congruent with Western categories, including sexual orientation labels (Asthana & Oostvogels, 2001; Banik, Fisher, & Anand, 2014; Boyce & Khanna, 2011; Closson et al, 2014; Khan, 2001; Kumta et al, 2010; Verma & Collumbien, 2004). For example, Welles et al (2011) conducted a cross-cultural online survey in the U.S. and India and documented that a larger percentage of Indian MSM did not identify themselves as either gay or bisexual in comparison to U.S. men, even though they engaged in sexual behaviors with other men. Interviews with middle aged MSM recruited in Mumbai demonstrated that a large number of participants did not relate to a sexual identity based on their sexual behaviors (Banik et al, 2014), in some ways parallel to the “down low” phenomenon among Black men in the U.S. (Dodge, Jeffries, & Sandfort, 2008; Millett, Malebranche, & Mason, 2005).…”
Section: Introductionmentioning
confidence: 99%